An investigation into the application of Austrian didactics and methods of elementary musical education in South African school - Nowotny, Ingrid Heidelinde (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1970)
Why teach music? To answer this question one has to be able to see the full value of musical education. One has to recognize its effect on the unfolding of character and personality on the one hand and, on the other, its value for the development and sharpening of the intellect. In ancient Greece, the cradle of Western culture, the significance of music for man, the people, and the state was frequently emphasized. The Greeks regarded music almost as a magic force, the inherent harmony of which was capable of transforming things and creating order by reconciling contrarieties. Similarly they believed that the power of music could restore the harmony in man's soul. Intro., p.1.
Keywords: School music -- Instruction and study -- South Africa; Music -- Study and teaching (Elementary); Music theory -- Elementary works